What is a crisis?: service user, carer and professional understandings of crisis: a Q-methodological approach - Davies, Kerry (2016)
Background. This topic was proposed by the Service User and Carer Advisory Panel (SUCAP) which informs and supports Clinical Psychology training at The University of Nottingham. The project developed due to their concern about the ambiguity of crisis. They suggested that their understandings may be different from that of professionals. The reconfiguration of acute mental health services influenced the nationwide implementation of community treatment alternatives. However, crisis has remained a poorly operationalised concept, which can lead to problems in clinical practice. An increase in empirical efforts has aimed to establish clarity and increase the clinical utility of definitions. Despite these efforts, little is known about how service users and carers understand crisis. As suggested by the SUCAP, it is unclear if there is commonality within understandings of crisis. Due to the multiple stakeholders, exploring understandings of crisis from multiple perspectives could be useful in clinical practice.